STUDI KUALITAS PERAIRAN BEBERAPA SUNGAI DI KABUPATEN BADUNG - I Made Sara Wijana (Bumi Lestari Journal of Environment)
A study on water quality of some rivers in Badung Regency (Dangkang River inBeringkit, Penet River in Ayunan, Mati River in Kuta, as well as Ayung River in Carang Sariand Bongkasa) was carried out in dry and wet seasons 2002. Aim of the study is to find thewater quality of those rivers benchmarked with Governor of Bali decree (decision) No.515/2000.Results of the study showed that water quality of Mati River is the worst. There areseven parameters in this river which did not pass the benchmark, namely odor, taste,phosphate, DO, fat, Fecal coli (E. coli) and coliform. Meanwhile, Ayung river had threeparameters (phosphate, fat and TDS), and Penet as well as Dangkang Rivers had twoparameters only (phosphate and fat) which didi not pass the benchmark. Water from all riverare found to be polluted by phosphate and fat either during dry or wet seasons.